2013
DOI: 10.1186/1472-6920-13-15
|View full text |Cite
|
Sign up to set email alerts
|

Communication training for advanced medical students improves information recall of medical laypersons in simulated informed consent talks – a randomized controlled trial

Abstract: BackgroundInformed consent talks are mandatory before invasive interventions. However, the patients’ information recall has been shown to be rather poor. We investigated, whether medical laypersons recalled more information items from a simulated informed consent talk after advanced medical students participated in a communication training aiming to reduce a layperson’s cognitive load.MethodsUsing a randomized, controlled, prospective cross-over-design, 30 5th and 6th year medical students were randomized into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 27 publications
0
16
0
Order By: Relevance
“…[23][24][25][26][27] Finally, interventions to improve information disclosure and patient-provider communication may be useful in discussion of transplantation with patients initiating hemodialysis, because these have shown benefit in patient comprehension of treatment options, risks, and benefits in other clinical settings. 8 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[23][24][25][26][27] Finally, interventions to improve information disclosure and patient-provider communication may be useful in discussion of transplantation with patients initiating hemodialysis, because these have shown benefit in patient comprehension of treatment options, risks, and benefits in other clinical settings. 8 …”
Section: Discussionmentioning
confidence: 99%
“…For example, in some clinical care and clinical research settings, providers have reported obtaining informed consent only for legal protection rather than patient understanding. 6,7 Although studies of patient knowledge after provision of medical information have shown that patient characteristics, such as age, race, or education, might affect patient understanding, 8 no studies have investigated patient perceptions of KTPI or factors associated with discordance between patient-reported and provider-reported KTPI.…”
mentioning
confidence: 99%
“…Patient characteristics include age, education, health literacy and anxiety . Information characteristics include modality (written vs aural), structure, number of instructions given and encounter length . Clinicians’ communication skills are also related to recall .…”
Section: Introductionmentioning
confidence: 99%
“…Studying related researches to training students showed that, in an interventional study which was conducted among two groups of students, the group that received communicational skills training at the end of the course had higher recall of information for taking informed consent. [ 21 ] One study used skills-based training for interns for taking informed consent, which resulted in statistically significant difference in the method of taking informed consent and also the total knowledge about the content of informed consent after training. [ 15 ]…”
Section: Discussionmentioning
confidence: 99%